Analysis of acoustic emission parameters of steel plate reinforcement effect on shearing zone of ECC-NC composite beams. (1st September 2022) - Li, Shengli; Hou, Jie; Guo, Pan; Zhang, Xiaoyu; Zhang, Pu
Highlights: AE monitoring can be an alternative to traditional methods. AET can implement health monitoring of steel plate reinforced ECC-NC composite beams. AE energy and Ib -value characteristics are more sensitive to early warning of steel plate reinforcement failure. The AE sensors are recommended to be arranged directly on the steel plate used for reinforcement. Abstract: The reinforcement effect evaluation of cement composite (ECC) normal concrete (NC) composite beams in steel plate reinforcement engineering has always been a difficulty in structural monitoring. As a kind of structural health monitoring (SHM) technology, acoustic emission technique (AET) can be used to analyze the structural failure mode, but it has not been carried out to select the optimal AE parameters and AE sensors arrangement to analyze the crack propagation of concrete structures and the early warning of reinforcement measures failure. And the traditional monitoring method also failed to realize the early warning of steel plate reinforcement failure. In this work, first, AET was used to monitor the four-point bending test of ECC-NC composite beams reinforced with steel plates. Then, the crack propagation process of the composite beam and the reinforcement effect of the steel plates are analyzed by using AE parameters. Finally, through the comparative analysis of AE parameters at different positions of the composite beam, the optimal AE parameters and the arrangement of AE sensors are selected. The results show that the AE ringing count fails to realize the early warning of steel plate reinforcement failure. The characteristics of AE energy, peak frequency, and Ib -value collected by the AE sensor arranged on the steel plate on the beam side can realize the analysis of the crack propagation process of the composite beam and the early warning of the failure of the steel plate reinforcement. The Ib -value and AE peak frequency change characteristics collected by the AE sensor directly arranged at the mid-span on the top of the composite beam cannot implement the crack propagation process of the composite beam and the early warning of steel plate reinforcement failure. It is not recommended to place the AE sensor at the top mid-span position of the composite beam. The RA-AF correlation distribution shows that the shear cracks are mainly generated during the bending process of ECC-NC composite beams reinforced with steel plates. The research on the optimal AE parameters and the arrangement of AE sensors has important academic significance and engineering application value for realizing AET monitoring of the crack propagation process of ECC-NC composite beams reinforced with steel plates and early warning of the steel plate reinforcement failure.